2016
DOI: 10.1038/ejcn.2016.249
|View full text |Cite
|
Sign up to set email alerts
|

Acute increases in serum colonic short-chain fatty acids elicited by inulin do not increase GLP-1 or PYY responses but may reduce ghrelin in lean and overweight humans

Abstract: BackgroundColonic fermentation of dietary-fibre to short-chain-fatty-acids (SCFA) influences appetite hormone secretion in animals, but SCFA production is excessive in obese animals. This suggests there may be resistance to the effect of SCFA on appetite-hormones in obesity.Objectivesto determine the effects of inulin (IN) and resistant-starch (RS) on postprandial SCFA, and gut hormone (GLP-1, PYY, and ghrelin) responses in healthy overweight/obese (OWO) vs lean (LN) humans.MethodsOvernight fasted participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 50 publications
2
39
2
Order By: Relevance
“…The consumption of soluble dietary fibre has been shown by different studies to increase the production of plasma glucagon-like peptide 1 (GLP1) and peptide YY (PYY), depending on the dose, usually when greater than 5 g [10][11][12][13][14]. In addition, the intake of soluble fibre can have an effect on ghrelin levels, decreasing their secretion in a healthy adult population [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The consumption of soluble dietary fibre has been shown by different studies to increase the production of plasma glucagon-like peptide 1 (GLP1) and peptide YY (PYY), depending on the dose, usually when greater than 5 g [10][11][12][13][14]. In addition, the intake of soluble fibre can have an effect on ghrelin levels, decreasing their secretion in a healthy adult population [12,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, the expression of other appetite‐related hormones, including NPY , AgRP , POMC , and CART , was also regulated by MOS treatment. It has been reported that SCFAs could play roles in regulating the metabolism via the gut–brain axis . Correlation analysis found that serum butyrate levels were negatively correlated with NPY expression ( r = –0.81, p < 0.01).…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, these results indicated that MOS treatment could inhibit WD‐induced body weight gain by upregulating the production of SCFAs, which mediate the expression of mediating appetite‐related hormones, and subsequently inhibiting energy intake. However, another study also demonstrated that SCFAs could possibly regulate the appetite by mediating the function of the vagus nerve or stimulating gut enteroendocrine L cells secreting PYY and GLP‐1 , which further regulate the expression of NPY and POMC . Future studies are needed to investigate whether MOS treatment could also have these underlying regulating effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations